Difference between revisions of "RMS amplitude"

From SEG Wiki
Jump to: navigation, search
Line 1: Line 1:
  <math>\sqrt{2}/2</math><math>x_RMS = \sqrt{\tfrac{1}{N} \sum_{i=1}^n x_i^2}                        </math><math>f_RMS = \sqrt{\tfrac{1}{T_2-T_1} \int_{T_1}^{T_2} [f(t)]^2 dt }</math><math>f_RMS = \sqrt{\tfrac{1}{T} \int_{0}^{T} [f(t)]^2 dt }</math><math>y(t) = Asin (2\pift+\varphi) = Asin(\omegat+\varphi)</math><math>Y_RMS = \sqrt{\tfrac{1}{T} \int_{0}^{T} [Asin(\omegat)]^2 dt}</math><math>      = A\sqrt{\tfrac{1}{T} \int_{0}^{T} \tfrac{1-cos(2\omegat)}{2} dt}</math><math>      = A\sqrt{\tfrac{1}{T} [\tfrac{T}{2} - \tfrac{sin(2\omegat)}{4\omega}]_0^T}</math><math>      = \tfrac{A}{\sqrt{2}}</math><math>=\sqrt{\frac{1}{N}\sum_{i=1}^nx_i^2}</math><math>x_RMS=\sqrt{\tfrac{1}{n}\sum_{i=1}^nx_i^2}                                                                    (1)
+
   
 +
<math>\sqrt{2}/2</math><math>x_RMS = \sqrt{\tfrac{1}{N} \sum_{i=1}^n x_i^2}                        </math><math>f_RMS = \sqrt{\tfrac{1}{T_2-T_1} \int_{T_1}^{T_2} [f(t)]^2 dt }</math><math>f_RMS = \sqrt{\tfrac{1}{T} \int_{0}^{T} [f(t)]^2 dt }</math><math>y(t) = Asin (2\pift+\varphi) = Asin(\omegat+\varphi)</math><math>Y_RMS = \sqrt{\tfrac{1}{T} \int_{0}^{T} [Asin(\omegat)]^2 dt}</math><math>      = A\sqrt{\tfrac{1}{T} \int_{0}^{T} \tfrac{1-cos(2\omegat)}{2} dt}</math><math>      = A\sqrt{\tfrac{1}{T} [\tfrac{T}{2} - \tfrac{sin(2\omegat)}{4\omega}]_0^T}</math><math>      = \tfrac{A}{\sqrt{2}}</math><math>=\sqrt{\frac{1}{N}\sum_{i=1}^nx_i^2}</math><math>x_RMS=\sqrt{\tfrac{1}{n}\sum_{i=1}^nx_i^2}                                                                    (1)
 
The RMS of the corresponding formula for a continuous waveform f(t) defined over the interval [T1, T2] is
 
The RMS of the corresponding formula for a continuous waveform f(t) defined over the interval [T1, T2] is
 
f_{RMS}=\sqrt{\tfrac{T_2}{T_1}\textstyle \int_{T_1}^{T_2} \displaystyle [f(t)]^2}dt            (2)
 
f_{RMS}=\sqrt{\tfrac{T_2}{T_1}\textstyle \int_{T_1}^{T_2} \displaystyle [f(t)]^2}dt            (2)

Revision as of 10:12, 21 October 2019

Failed to parse (unknown function "\pift"): {\displaystyle y(t) = Asin (2\pift+\varphi) = Asin(\omegat+\varphi)} Failed to parse (unknown function "\omegat"): {\displaystyle Y_RMS = \sqrt{\tfrac{1}{T} \int_{0}^{T} [Asin(\omegat)]^2 dt}} Failed to parse (unknown function "\omegat"): {\displaystyle = A\sqrt{\tfrac{1}{T} \int_{0}^{T} \tfrac{1-cos(2\omegat)}{2} dt}} Failed to parse (unknown function "\omegat"): {\displaystyle = A\sqrt{\tfrac{1}{T} [\tfrac{T}{2} - \tfrac{sin(2\omegat)}{4\omega}]_0^T}} Failed to parse (syntax error): {\displaystyle x_RMS=\sqrt{\tfrac{1}{n}\sum_{i=1}^nx_i^2} (1) The RMS of the corresponding formula for a continuous waveform f(t) defined over the interval [T1, T2] is f_{RMS}=\sqrt{\tfrac{T_2}{T_1}\textstyle \int_{T_1}^{T_2} \displaystyle [f(t)]^2}dt (2) and the RMS for a function over all time is f_{RMS}=\sqrt{\tfrac{1}{T}\int_{0}^{T} [f(t)]^2}dt (3) For a sine wave y(t)=A sin⁡(2πft+φ)=Asin(ωt+φ) (4) where y is displacement, t is time, f is frequency, and A is amplitude (the peak deviation of the function from zero) Y_{RMS}=\sqrt{\tfrac{1}{T}\int_{0}^{T} [Asin(\omegat)]^2dt} =A\sqrt{\tfrac{1}{T}\int\limits_{0}^{T} \tfrac{1-cos(2\omegat)}{2}dt} =A\sqrt{\tfrac{1}{T}[\tfrac{T}{2}-\tfrac{sin(2\omegat)}{4\omega}]_0^T} =\tfrac{A}{\sqrt{2}} (5) }